Proceedings of the Fourth International Conference in Ocean Engineering (ICOE2018) Volume 2 - Murali, K.; Sriram, V.; Samad, Abdus; Saha, Nilanjan (Lecture Notes in Civil Engineering, 2019)
This book comprises selected proceedings of the Fourth International Conference in Ocean Engineering (ICOE2018), focusing on emerging opportunities and challenges in the field of ocean engineering and offshore structures. It includes state-of-the-art content from leading international experts, making it a valuable resource for researchers and practicing engineers alike. .